Researching the Level of Diffusion of Selective Management Accounting Techniques by Bangladeshi Firms - Nikhil Chandra Shil; Mahfuzul Hoque; Mahmuda Akter (Journal of Accounting and Management Information Systems (JAMIS), 2015)
Application of different management accounting techniques in corporate management sets the tune of the respective corporate in terms of its level of competition, needs for critical decision making, complexity of operations, and stages of different life cycles. This paper applies a quantitative research methodology based on structured questionnaire survey to highlight the diffusion status of different management accounting techniques in selective manufacturing companies operating in Bangladesh. As the manufacturing sector in Bangladesh is getting stronger day by day in terms of generating employment, contributing to GDP, mobilizing resources, and improving other economic factors; a sound management accounting practices via application of different management accounting techniques receive increased attention. The outcome of the paper will definitely help the management accounting practitioners, educators and researchers for policy implications. International community will also be benefited from the research outcome demonstrated by Bangladeshi firms due to the perceived importance of Bangladesh in newly defined economic zone led by India and China.
Keywords: M41; 650; Diffusion; management accounting techniques; management accounting practices; Bangladesh